2011
DOI: 10.4236/jep.2011.23026
|View full text |Cite
|
Sign up to set email alerts
|

Agrochemicals and the Ghanaian Environment, a Review

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 21 publications
1
41
0
1
Order By: Relevance
“…The average awareness score of farmers interviewed was 58% indicating that maize farmers in the study area are moderately aware of agrochemical usage and its health implications. The study confirmed the findings of Fianko et al [22] that there is considerable evidence that farmers have overused agrochemicals especially pesticides. It is also consistent with Omari [4] findings that farmers have a low level of awareness of the hazards associated with the use of agrochemicals.…”
Section: Level Of Awareness Of Health Implications Of Agrochemicalsupporting
confidence: 81%
“…The average awareness score of farmers interviewed was 58% indicating that maize farmers in the study area are moderately aware of agrochemical usage and its health implications. The study confirmed the findings of Fianko et al [22] that there is considerable evidence that farmers have overused agrochemicals especially pesticides. It is also consistent with Omari [4] findings that farmers have a low level of awareness of the hazards associated with the use of agrochemicals.…”
Section: Level Of Awareness Of Health Implications Of Agrochemicalsupporting
confidence: 81%
“…A similar study conducted by Kihampa et al (2010) in Tanzania, to assess the level of organochlorine insecticide residues in soil from tomato fields, revealed that DDT metabolites 4,4-DDD and 4,4-DDE were detected in 53 % of the soil samples analysed. A systematic review of studies done in Ghana, a neighbouring country of Togo, to give an integrated picture of agrochemicals, especially exposure of humans, animals, plants, water, soil, sediment and atmosphere, revealed contamination of the Ghanaian environment (Fianko et al 2011). Numerous studies have reported the persistence of organochlorine insecticides in soil and water of cultivated land worldwide (Dem et al 2007;Jamal 2011).…”
Section: Methodsmentioning
confidence: 98%
“…As a result the application of synthetic pesticides have been a measure to control pests and diseases in order to increase yields (Dankyi et al 2014). However, regular and repeated application of pesticides on cocoa trees throughout cocoa seasons, coupled with the indiscriminate use and inappropriate handling of the chemicals by farmers has often been associated with unintended environmental and human health consequences (Fianko et al 2011;Dankyi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of the natural environment with pesticides especially organochlorine have been a major concern to researchers because of their toxicity and threat to human, soil, water, animal and plant health (Afful et al 2010;Fianko et al 2011). Pesticides reaching the soil after spraying may affect soil quality by disturbing some soil organisms such as earthworms, microbes and natural enemies which acts as decomposers (Ntiamoah and Afrane 2008).…”
Section: Introductionmentioning
confidence: 99%